Gender Disparities in Sport Science: A Research Gap Analysis of Female Athletes - Lianingsih, Nestia; Irman, Dede (International Journal of Health, Medicine, and Sports, 2025)
In recent decades, women’s participation in sports has grown significantly, reaching near parity with men in major competitions such as the 2024 Paris Olympics. However, this progress has not been mirrored in sports science research, where women remain underrepresented both as research subjects and academic leaders. This study aims to analyze the gender gap in sports science research, particularly regarding female athletes, by conducting a descriptive qualitative study using a literature review approach. Data were collected from reputable academic journals indexed in Scopus, Web of Science, and Google Scholar, as well as official reports from international sports organizations. Thematic analysis was used to categorize findings into key themes, including injury risks, nutritional disparities, and scientific leadership. The results show that only 6% to 9% of sports science studies exclusively focus on female athletes, while female participation in mixed studies ranges from 35% to 39%. Furthermore, female leadership in scientific publications remains below 30%. This underrepresentation creates a significant knowledge gap, leading to biased recommendations in training, nutrition, and injury prevention, as most guidelines are based on male physiology. The study also highlights the higher risk of injuries, such as anterior cruciate ligament (ACL) tears, among female athletes, often overlooked in research that ignores hormonal fluctuations like the menstrual cycle. Initiatives such as the Female Athlete Science and Translational Research (FASTR) and the Global Alliance for Female Athletes (GAFA) have been launched to address these disparities, yet broader support is needed. In conclusion, increasing women’s representation in research and leadership is crucial to developing inclusive, evidence-based practices that better support female athletes’ health and performance.